Accelerating the in vitro emulation of Alzheimer’s disease-associated phenotypes using a novel 3D blood-brain barrier neurosphere co-culture model - Ko, Eunkyung Clare; Spitz, Sarah; Pramotton, Francesca Michela; Barr, Olivia M.; Xu, Ciana; Pavlou, Georgios; Zhang, Shun; Tsai, Alice; Maaser-Hecker, Anna; Jorfi, Mehdi; Choi, Se Hoon; Tanzi, Rudolph E.; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
High failure rates in clinical trials for neurodegenerative disorders such as Alzheimer’s disease have been linked to an insufficient predictive validity of current animal-based disease models. This has created an increasing demand for alternative, human-based models capable of emulating key pathological phenotypes in vitro. Here, a three-dimensional Alzheimer’s disease model was developed using a compartmentalized microfluidic device that combines a self-assembled microvascular network of the human blood-brain barrier with neurospheres derived from Alzheimer’s disease-specific neural progenitor cells. To shorten microfluidic co-culture times, neurospheres were pre-differentiated for 21 days to express Alzheimer’s disease-specific pathological phenotypes prior to the introduction into the microfluidic device. In agreement with post-mortem studies and Alzheimer’s disease in vivo models, after 7 days of co-culture with pre-differentiated Alzheimer’s disease-specific neurospheres, the three-dimensional blood-brain barrier network exhibited significant changes in barrier permeability and morphology. Furthermore, vascular networks in co-culture with Alzheimer’s disease-specific microtissues displayed localized β-amyloid deposition. Thus, by interconnecting a microvascular network of the blood-brain barrier with pre-differentiated neurospheres the presented model holds immense potential for replicating key neurovascular phenotypes of neurodegenerative disorders in vitro.